ENGINEERING DREAMS, ENDURING STRESS: THE HEAVY TOLL OF STRESS ON ENGINEERING STUDENTS: A CROSS-SECTIONAL STUDIES - Janhavi Sarva, Kanika Gupta, Keshav Aggarwal, Ruchita Dixit, Amol R. Patil, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: The pressure of professional courses like engineering and medicine often takes a toll on students, leading to stress, anxiety, and health issues. Heavy workloads and packed schedules disrupt sleep and eating habits, worsening stress over time. This study analyses stress factors among engineering students through a survey-based quantitative approach.